DETERMINASI MAKROEKONOMI TERHADAP HARGA SAHAM SEKTOR PERTAMBANGAN DI INDONESIA - Putra, Angga; As’ari, Erham; Fadhi, Khoirul (Sekolah Tinggi Ekonomi Dan Bisnis Islam Darussalam, 2021)
This research is about the effect of the BI Rate, Exchange Rate, Industrial Production Index (IPI) and World Oil Prices on the share price of the mining sector in the Indonesian Syariah Stock Index (ISSI). The research objective is to determine the magnitude of the effect of the BI Rate, Exchange Rate, Industrial Production Index (IPI) and World Oil Prices on ISSI mining sector stock price fluctuations and the magnitude of the effect of each of these variables on each entity. The data used is panel data consisting of monthly data from June 2011 to December 2018. The author estimates the independent variables in the form of the BI Rate, Exchange Rate, Industrial Production Index (IPI) and World Oil Prices to the mining sector stock prices at ISSI using regression estimates Fixed Effect Model (FEM). The results showed that the variable BI Rate, IPI and world oil prices significantly influence the stock price of the mining sector at ISSI. While the exchange rate has no significant negative effect.